m-RECIST at 1 month and Child A are survival predictors after percutaneous ethanol injection of hepatocellular carcinoma - Mauricio F. Silva; Flair J. Carrilho; Denise C. Paranaguá-Vezozzo; Luciana T. Campos; Lucas S. Nacif; Marcio A. Diniz; Alberto Q. Farias; Venancio A.F. Alves; Luis A.C. D’Alburquerque; Suzane K. Ono (Annals of Hepatology, 2014)
Background and aims. Percutaneous ethanol injection (PEI) is a well-established therapeutic option in patients with cirrhosis and hepatocellular carcinoma (HCC). The modified-Response Evaluation Criteria in Solid Tumors (m-RECIST) are an important tool for the assessment of HCC response to therapy. The aim was to evaluate whether HCC response according to the m-RECIST criteria could be an effective predictor of long-term survival in Barcelona Clinic Liver Cancer (BCLC) stage 0 and A HCC patients undergoing PEI.Material and methods. 79 patients were followed-up for median time of 26.8 months. HCC diagnosis was based on the current guidelines of the American Association for Study of the Liver Diseases (AASLD) and European Association for Study of the Liver (EASL). Patient survival was calculated from the first PEI session to the end of the follow-up.Results. The 1-, 3-, and 5-year overall survival rates were 79, 48 and 37%, respectively. In the multivariate analysis, Child-Pugh-Turcotte (CPT) (p = 0.022) and the response to m-RECIST criteria (p = 0.016) were associated with patient survival. CPT A patients who achieved Complete Response (CR) 1 month after PEI presented a 5-year survival rate of 55%. By contrast, the worst scenario, the group with CPT B but without CR had a 5-year survival rate of 9%, while the group with either CPT A or CR as a survival predictor had a 5-year survival rate of 31%. In conclusion, in BCLC stage 0 and A HCC-patients, m-RECIST at 1 month and Child A may predict survival rates after PEI.